Muscle strength, but not body mass index, is associated with mortality in patients with non‐alcoholic fatty liver disease. Issue 5 (26th August 2022) - Charatcharoenwitthaya, Phunchai; Karaketklang, Khemajira; Aekplakorn, Wichai
Abstract: Background: Whether adiposity and muscle function are associated with mortality risk in patients with non‐alcoholic fatty liver disease (NAFLD) remains unknown. We examine the independent and combined associations of body mass index (BMI) and muscle strength with overall mortality in individuals with NAFLD. Methods: We analysed data from 7083 participants with NAFLD in the Thai National Health Examination Survey and their linked mortality. NAFLD was defined using a lipid accumulation product in participants without significant alcohol intake. Poor muscle strength was defined by handgrip strength of <28 kg for men and <18 kg for women, according to the Asian Working Group on Sarcopenia. The Cox proportional‐hazards model was constructed to estimate the adjusted hazard ratio (aHR) for overall mortality. Results: The mean age was 49.3 ± 13.2 years, and 69.4% of subjects were women. According to the Asian‐specific criteria, 1276 individuals (18.0%) were classified as lean NAFLD (BMI 18.5–22.9 kg/m 2 ), 1465 (20.7%) were overweight NAFLD (BMI 23–24.9 kg/m 2 ), and 4342 (61.3%) were obese NAFLD (BMI ≥ 25 kg/m 2 ). Over 60 432 person‐years, 843 participants died. In Cox models adjusted for physiologic, lifestyle, and comorbid factors, individuals with lean NAFLD [aHR 1.18, 95% confidence interval (CI): 0.95–1.48; P  = 0.138] and subjects with overweight NAFLD (aHR 1.28, 95% CI: 0.89–1.84; P  = 0.158) had mortality risk estimates similar to their obese counterparts, whereas participants with lower handgrip strength had significantly higher mortality risk than those with higher handgrip strength in men and women. Compared with obese individuals with the highest handgrip strength, elevated mortality risk was observed among men (aHR 3.21, 95% CI: 1.35–7.62, P  = 0.011) and women (aHR 2.22, 95% CI, 1.25–3.93, P  = 0.009) with poor muscle strength. Among men, poor muscle strength was associated with increased risk of mortality with obese NAFLD (aHR 3.94, 95% CI, 1.38–11.3, P  = 0.013), overweight NAFLD (aHR 2.93, 95% CI, 1.19–7.19, P  = 0.021), and lean NAFLD (aHR 2.78, 95% CI, 0.93–8.32, P  = 0.065). Among women, poor muscle strength was associated with increased mortality risk with obese NAFLD (aHR 2.25, 95% CI, 1.06–4.76, P  = 0.036), overweight NAFLD (aHR 1.69, 95% CI, 0.81–3.51, P  = 0.153), and lean NAFLD (aHR 2.47, 95% CI, 1.06–5.73, P  = 0.037). Conclusions: In this nationwide cohort of individuals with NAFLD, muscle strength, but not BMI, was independently associated with long‐term overall mortality. Measuring handgrip strength can be a simple, non‐invasive risk stratification approach for overall mortality in patients with NAFLD.